PENGARUH REWARD DAN PUNISHMENT TERHADAP SEMANGAT KERJA PEGAWAI PADA DINAS DP3AP2KB KABUPATEN BIMA - Mubarak, Rifky; -, Wulandari (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2022)
Abstract This study aims to determine the reward and punishment of employee morale at the office of women's empowerment, child protection, population control and family planning (DP3AP2KB) Bima Regency. Where the sample used was 36 people using purposive sampling, namely only Asn employees. The results of the multiple regression test show that every increase of 1 unit of reward variable will affect work morale by 0.316 and every increase of 1 unit of punishment variable will affect work morale by 0.498. The correlation coefficient value of 0.58 means that the influence of the independent variable on the dependent variable has moderate influence. The value of the coefficient of determination is 33.6%. Employee morale (Y) is influenced by Reward (X1) and Punishment (X2). The results of the t and F tests show that there is a significant effect between reward and punishment on work morale. Keywords: reward, punishment, work spirit.